Meteorological observations during POLARSTERN cruises (ANT-I/1 et seq) - Schmithüsen, Holger; König-Langlo, Gert (PANGAEA, 2025)
The meteorological observatory Polarstern issues synoptical reports every 3 hours during times of ship operation. The reports are distritubed via global networks of the World Meteorological Organisation. From December 1982 until December 2024 designated weather observers were onboard to include manual observations in the reports. Since December 2024 the nautical officers of Polarstern are on duty for the manual observations. For times that are not covered by an observer automatic reports are issued. All observations are made in compliance with standards of the World Meteorological Organisation and those of the German Weather Service (DWD). This dataset compiles all datasets with synoptical reports from all Polarstern cruises.